(untitled) (Journal of Information Technologies in Education (ITE), 2012)
In this article is described the information an experience of introduction in educational process of pedagogical program systems of support of practical activities for example pedagogical software "Algebra, 8 class" and also aspect of formation of mathematical activity during algebra studying.